Pemanfaatan TikTok sebagai Media Informasi Digital pada DPMPTSP Kabupaten Madiun - Muha Nanda Sho'im; Sofyan Triono; Mei Lenawati (CV. Multi Kreasi Media, 2026)
The development of information and communication technology has encouraged government agencies to adapt in conveying public information, one of which is through the use of social media. TikTok as a short video-based platform is considered effective in attracting public attention and disseminating information quickly, interactively, and easily accessible. The purpose of this internship is to determine the strategy for utilizing the TikTok account of the Madiun Regency DPMPTSP in conveying public service information, increasing interaction with the community, and supporting transparency and openness of information. The method used is the SUS (System Usability Scale) method by distributing questionnaires to DPMPTSP Madiun Regency employees and students of PGRI Madiun University, as well as documentation of social media management activities within the agency. The results obtained indicate that the use of TikTok can increase the reach of information related to licensing services, investments, and DPMPTSP activity programs.